Histological and immunohistochemical study of the potential therapeutic impacts of bone marrow mesenchymal stem cells and exosomes for sciatic nerve crush injury model in rats. (2nd October 2018) - El-Azab, Nahla El-Eraky; El-Mahalaway, Abeer M.; Mostafa, Ola; Sabry, Dina
ABSTRACT: The aim was to evaluate the potential effect of bone marrow-derived mesenchymal stem cells (BMSC) and BMSC-EX in the sciatic nerve injury. Forty-five rats were divided into four groups, i.e. Group I control no surgery or treatment, Group II sciatic nerve crush surgery and 1 week post-surgery, Group III sciatic nerve crush injury was treated with BMSC, and Group IV sciatic nerve crush injury was treated with BMSC-EX. All animal groups were euthanized 2 weeks after treatment. Sciatic nerves were examined histologically and immunohistochemically. Group II showed various histological changes, i.e. vacuolation, degeneration and loss of nerve fibers. Group II showed a significant increase in collagen fibers, but with significant reduction in osmium tetroxide (OsO4 )-stained myelin sheaths and neurofilament immunostaining compared to Group I. Group II also revealed distortion and disruption of myelinated nerve fibers. Groups III and IV showed significant improvement of both histological and immunohistochemical changes in Group II. BMSC and BMSC-EX were shown to improve axonal regeneration.